Toluene Can Disrupt Rat Ovarian Follicullogenesis and Steroidogenesis and Induce Both Autophagy and Apoptosis - Abdulkarem Alrezaki (MDPI AG, 2021)
Toluene has been shown to be highly toxic to humans and animals and can cause damage to various tissues. However, studies reporting its effects on ovarian function are still limited. In this study, we investigated the in vivo effect of toluene using female Wistar rats. We found that toluene exposure decreased ovarian weight and affected ovarian structure by increasing the number of abnormally growing follicles. Moreover, it significantly increased progesterone and testosterone levels. We also showed that toluene exposure decreased GDF-9 protein and its encoding gene. In addition, it inhibited the expression of most of the genes involved in granulosa cell proliferation and differentiation, such as Insl3, ccnd2 and actb. The TUNEL assay showed that apoptosis occurred at the middle and high doses only (4000 and 8000 ppm, respectively), whereas no effect was observed at the low dose (2000 ppm). Interestingly, we showed that toluene exposure induced autophagy as LC3 protein and its encoding gene significantly increased for all doses of treatment. These results may suggest that the activation of autophagy at a low dose of exposure was to protect ovarian cells against death by inhibiting apoptosis, whereas its activation at high doses of exposure triggered apoptosis leading to cell death.